Dorsal interacting protein 3 potentiates activation by Drosophila Rel homology domain proteins. - Ratnaparkhi, G.S.; Duong, H.A.; Courey, A.J. (Developmental and Comparative Immunology, 2008)
Dorsal interacting protein 3 (Dip3) contains a MADF DNA-binding domain and a BESS protein interaction domain. The Dip3 BESS domain was previously shown to bind to the Dorsal Rel homology domain. We show here that Dip3 also binds to the Relish Rel homology domain and enhances Rel family transcription factor function in both dorsoventral patterning and the immune response. While Dip3 is not essential, Dip3 mutations enhance the embryonic patterning defects that result from dorsal haplo-insufficiency, indicating that Dip3 may render dorsoventral patterning more robust. Dip3 is also required for optimal resistance to immune challenge since Dip3 mutant adults and larvae infected with bacteria have shortened lifetimes relative to infected wild-type flies. Furthermore, the mutant larvae exhibit significantly reduced expression of antimicrobial defense genes. Chromatin immunoprecipitation experiments in S2 cells indicate the presence of Dip3 at the promoters of these genes, and this binding requires the presence of Rel proteins at these promoters.